Singapore Business: Who Survive the Crisis? - Cheang, Kum Wai (2010)
The economic downturn in 2009 has affected people and countries across the world. As Singapore’s economy is extremely dependent on foreign trade and exports, the economic downturn has affected many sectors of the economy. Using financial data of 50 Singapore companies listed in Singapore Exchange, uneven impacts of the turndown on companies in various sectors was evident for the period under review. Companies with businesses related to technology, tourism, transport and logistics, waste management, mid to high end food segment and property sectors were adversely affected. On the other hand, companies with businesses related to banking, public transportation, telecommunication services, infrastructure and construction sectors, water treatment, medical and health sector, supermarket retail and mass market food segment were relatively resilient amid the economic downturn. In addition, companies with diverse businesses in different sectors performed relatively well for the period under review.